Orthostatic hypotension is associated with new-onset atrial fibrillation: Systemic review and meta-analysis - Prasitlumkum, Narut (Indian Heart J, 2019)
INTRODUCTION: Orthostatic hypotension (OH) is common among elderly patients. Its presence may herald severe underlying comorbidities and be associated with a higher risk of mortality. Interestingly, recent studies suggest that OH is associated with new-onset atrial fibrillation (AF). However, a systematic review and meta-analysis of the literature has not been performed. We assessed the association between AF and OH through a systematic review of the literature and a meta-analysis. METHODS: We comprehensively searched the databases of MEDLINE and EMBASE from inception to November 2018. Published prospective or retrospective cohort studies that compared new-onset AF between male patients with and without OH were included. Data from each study were combined using the random-effects, generic inverse-variance method of DerSimonian and Laird to calculate risk ratios and 95% confidence intervals. RESULTS: Four studies from October 2010 to March 2018 were included in the meta-analysis involving 76,963 subjects (of which 3318 were diagnosed with OH). The presence of OH was associated with new-onset AF (pooled risk ratio 1.48; 95% confidence interval [1.21, 1.81], p?< 0.001; I2 = 69.4%). In hypertensive patients, analysis revealed an association between OH and the occurrence of new-onset AF (OR 1.46; 95% CI [1.27, 1.68], p < 0.001 with I2 = 0). CONCLUSIONS: OH was associated with new-onset AF up to 1.5-fold compared with those subjects without OH. The interplay between OH and AF is likely bidirectional.